THE EFFECT OF SHARIA SYSTEM ON INDIVIDUAL ABILITY AND WORK ACHIEVEMENT IN SME BUSINESS (CASE STUDY OF UD SANIJA BAKERI CIREBON PLUMBON) - Edi Gunawan; Aen Fariah (Journal of Social Science, 2020)
Various ways are taken by the company in order to survive and develop in its operations process. One of them is related to productivity improvement programs, among others, the first covers the dynamics of organizational structure, the second covers processes in HRM and the third covers the mechanism of HR implementation. The ability or ability refers to an individual's capacity to do various tasks in a job. Islam has provided very clear guidance. Kafa'ah or expertise and skills are obtained through education, training, and experience. Himmatul 'Amal or a high work ethic was achieved by making worship motivation the main driver in addition to reward and punishment motivations as well as material gains. And Trust or trustworthiness and responsibility are obtained by making monotheism as the main driving force and controller of behavior. The purpose of this study is to improve and maintain the quality of individual employee abilities and work performance. One way to maintain and improve individual employee abilities and work performance is to hold intensive job training for employees who have a working period of at least about 1 year. This research is quantitative research. Quantitative research methods can be interpreted as a research method based on the philosophy of positivism, used to examine a particular population or sample, data collection using research instruments, statistical data analysis, to test the hypotheses that have been set. Based on this research the equation results can be obtained as follows: From the results of the F test that has been done, it can be seen that there is an influence of individual ability and work performance on work productivity at UD Sanija Bakeri Plumbon Cirebon. This is indicated by the calculated F value greater than F table or the significance of F smaller than the alpha value Keywords: Sharia System, Individual Capability, Job Performance